2018
DOI: 10.3855/jidc.9486
|View full text |Cite
|
Sign up to set email alerts
|

Role of efflux pump and OprD porin expression in carbapenem resistance of Pseudomonas aeruginosa clinical isolates

Abstract: Introduction: In recent years, the prevalence of multidrug-resistant P. aeruginosa has remarkably increased. Thus, we wanted to investigate the carbapenem resistance mechanisms and clonal relationship among 80 carbapenem-resistant P. aeruginosa strains. Methodology: Carbapenemase production was detected using the Modified Hodge Test (MHT), EDTA combined disc method (ECD), and PCR. Expression levels of efflux and porin genes were mesured by real-time reverse transcription PCR. Clonal relationship of the isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
3
10
1
Order By: Relevance
“…39 Although the MexXY-OprM system is known as a substantial element in aminoglycoside resistance in only P. aeruginosa, 40 it is also over-expressed in multi-drug resistant P. aeruginosa 41 and similar reports to our study have shown its over-expression in carbapenemresistant P. aeruginosa strains. 7,42,43 MexAB-OprM over-expression was observed in 21.8% of the isolates, concurring with Xavier and co-workers. 44 In contrast, Dantas et al 7 and Chalhoub et al 32 reported a much higher frequency of MexAB-OprM over-expression in P. aeruginosa isolates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…39 Although the MexXY-OprM system is known as a substantial element in aminoglycoside resistance in only P. aeruginosa, 40 it is also over-expressed in multi-drug resistant P. aeruginosa 41 and similar reports to our study have shown its over-expression in carbapenemresistant P. aeruginosa strains. 7,42,43 MexAB-OprM over-expression was observed in 21.8% of the isolates, concurring with Xavier and co-workers. 44 In contrast, Dantas et al 7 and Chalhoub et al 32 reported a much higher frequency of MexAB-OprM over-expression in P. aeruginosa isolates.…”
Section: Discussionsupporting
confidence: 87%
“…44 In contrast, Dantas et al 7 and Chalhoub et al 32 reported a much higher frequency of MexAB-OprM over-expression in P. aeruginosa isolates. Surprisingly, no down-regulation of oprD was detected in this study, which could be claimed to the presence of mutations eg, in loops L2 and L3 as described by Muderris et al 45 However, Chalhoub et al found no role for oprD mutation in high-level resistance compared to efflux pump overexpression. 32 Finding bacterial genetic similarity and relatedness is crucial for cross-infection assessment, for which the value of various genotyping techniques has been recognized.…”
Section: Discussioncontrasting
confidence: 56%
“…The modes of antibiotic resistance in P. aeruginosa may be classified into three categories, including (i) adaptive (i.e., biofilm formation, dormant forms), (ii) intrinsic (see Table 2), and (iii) acquired resistance mechanisms (mutation or acquisition of integrons, plasmids, prophages, and transposons by the means of HGT), resulting in a rich and diverse resistome [161]. The occurrence of mutations may lead to antibiotic uptake reduction, antibiotic target modifications, and over-expression of both efflux pumps system and antibiotic inactivating enzymes [162][163][164]. In essence-apart from the fluoroquinolones (who present with excellent oral bioavailability)-all of the present therapeutic alternatives for P. aeruginosa need to be administered parenterally [165].…”
Section: Intrinsic Resistance and Main Therapeutic Alternatives In Pmentioning
confidence: 99%
“…Intrinsic resistance and relevant therapeutic alternatives in Pseudomonas infections[159][160][161][162][163][164][165].…”
mentioning
confidence: 99%
“…In our country, most common carbapenem resistance mechanisms in P. aeruginosa infection are the ones mediated by metalloβ-lactamase (MBL) and OXA-23 carbapenemase enzymes but also oprD downregulation and mexB, mexY, and mexD overexpression were demonstrated. [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%